Corporate effective tax rates: a study on Malaysian public listed companies / Rohaya Md Noor, Nor'Azam Mastuki and Barjoyai Bardai - Bardai, Barjoyai (Accounting Research Institute (ARI) & Faculty of Accountancy, 2008)
This study examines corporate effective tax rates (ETRs) of large Malaysian listed companies during the new tax regime, and further investigates the relationship between corporate ETRs and their attributes. The goal of this study is to compare the effective tax rate effectively experienced by each company within and across sectors, and to provide evidence for factors that cause corporate ETRs to diverge from the statutory tax rate (STR).